Watch this space - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The topic of ICTs and rural development is still in the phase of the anecdote. Spore has reported over the years of how readers use the Internet . Remember the chicken farmer in Senegal who sold his 3,000 hens by using the Internet café...